2005
DOI: 10.2135/cropsci2004.0664
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Molecular Analysis of Oleate Content in the Mutant Soybean Line M23

Abstract: the -6 position mediated by the enzyme -6 fatty acid desaturase. Okuley et al. (1994) isolated the cDNA en-Soybean [Glycine max (L.) Merr.] oil with elevated oleate content coding the microsomal -6 fatty acid desaturase from would be useful for food and industrial applications that require increased oxidative stability. The first objective of this study was to Arabidopsis thaliana (L.) Heynh. as the Fad2 gene. Hepdetermine if molecular selection for the Fad2-1 deletion associated pard et al. (1996) found two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 20 publications
6
61
1
2
Order By: Relevance
“…In the soybean M23 mutant, the mid-oleic acid phenotype is associated with a lesion in one of the FAD2-1 genes (Alt et al, 2005a). However, even under optimal environmental conditions, the M23 genotype and the other mid-oleic acid genotypes require pyramiding of multiple genetic alleles for full penetration of the mid-oleic acid phe- notype (Bachlava et al, 2008b;Monteros et al, 2008).…”
Section: High Oleic Acid Soybean Oilmentioning
confidence: 99%
“…In the soybean M23 mutant, the mid-oleic acid phenotype is associated with a lesion in one of the FAD2-1 genes (Alt et al, 2005a). However, even under optimal environmental conditions, the M23 genotype and the other mid-oleic acid genotypes require pyramiding of multiple genetic alleles for full penetration of the mid-oleic acid phe- notype (Bachlava et al, 2008b;Monteros et al, 2008).…”
Section: High Oleic Acid Soybean Oilmentioning
confidence: 99%
“…Several soybean cultivars with increased oleate content are available, one of which is the midoleate mutant line M23 (Rahman et al, 1994) derived from x-ray mutagenized seed of the Bay soybean cultivar. Genetic studies indicated that the midoleate pheno- type of M23 is associated with the deletion of FAD2-1A (Alt et al, 2005;Sandhu et al, 2007;Anai et al, 2008). Given the agronomic importance of M23 in current breeding programs (Scherder et al, 2008) for increased seed oleate content, CGH could also be utilized to define the presence of other genetic lesions in the M23 genome, in addition to the previously reported FAD2-1A deletion.…”
Section: Fn Mutants With Visual Phenotypesmentioning
confidence: 99%
“…The mid-oleate content of the two MO parents, AX18896-2 and AX18895-6, was derived from M23, a mid-oleate mutant line with the ol allele developed at Saga University, Japan (Rahman et al, 1994;Takagi and Rahman, 1996;Alt et al, 2005). In additional to the ol allele, the two MO parents had, on the average, 25% of their genetic background from M23 because they were two crossing generations away from the mutant line.…”
Section: Methodsmentioning
confidence: 99%
“…Sandhu et al (2007) determined that the Fad2-1 modification producing mid-oleate content in M23 was caused by a deletion of the Fad2-1a gene and that the Fad2-1b gene was not altered. Alt et al (2005) with a range of 252 to 424 g kg -1 , and the mean for olol was 394 g kg -1 with a range of 350 to 451 g kg -1 . The overlapping ranges of oleate content among the three genotypes indicated the presence of modifying genes for oleate content.…”
Section: Inheritance Of Mid-oleatementioning
confidence: 98%